A revision of the Hawaiian and Wake Island species of the genus Conchopus Takagi (Diptera, Dolichopodidae) - Masunaga, Kazuhiro; Saigusa, Toyohei (Zootaxa, 2010)
Six shore-dwelling species of the rectus group of the genus Conchopus Takagi are recognized from the Hawaiian and Wake Islands, including five new species. Conchopus is restricted to this species group herein. Contrary to some earlier records, C. acrosticalis (Parent, 1937) occurs only on four of the Hawaiian Islands (Hawai‘i, Maui, Lāna‘i, and Moloka‘i). The new species are distributed as follows: C. ciliatus sp. nov. (Hawai‘i, Maui, O‘ahu and Lisianski Is.); C. crassinervis sp. nov. (Kaua‘i); C. minutus sp. nov. (Hawai‘i, Maui, Lāna‘i, O‘ahu, and French Frigate Shoals); C. menehune sp. nov. (Kaua‘i and Nihoa Is.); and C. pacificus sp. nov. (Hawai‘i, O‘ahu, Kaua‘i, and Wake Is). A key to the males of all known species of the rectus group is provided.